2013
DOI: 10.1152/ajprenal.00329.2012
|View full text |Cite
|
Sign up to set email alerts
|

Retention of fetuin-A in renal tubular lumen protects the kidney from nephrocalcinosis in rats

Abstract: The serum glycoprotein fetuin-A is an important inhibitor of extraosseous calcification. The importance of fetuin-A has been confirmed in fetuin-A null mice, which develop widespread extraosseous calcification including the kidney. However, the mechanism how fetuin-A protects kidneys from nephrocalcinosis remains uncertain. Here, we demonstrate that intratubular fetuin-A plays a role in the prevention of nephrocalcinosis in the proximal tubules. Although normal rat kidney did not express mRNA for fetuin-A, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 24 publications
6
32
0
1
Order By: Relevance
“…Higher excretion of fetuin-A into urine has been reported to reflect the insulin resistance and inflammatory responses in obesity and type 2 diabetes [43] and it may reflect the increase in the serum levels of fetuin-A and alterations in the changes in the permeability of glomerular capillaries. Fetuin-A is reported to pass through the slit diaphragm and re-introduced to proximal tubular cells by megalin-mediated endocytosis [44]. Zhou et al also reported that urinary exosomal fetuin-A was increased in the rats treated with cisplatin injection and in the ICU patients with acute kidney injury [45].…”
Section: Discussionmentioning
confidence: 99%
“…Higher excretion of fetuin-A into urine has been reported to reflect the insulin resistance and inflammatory responses in obesity and type 2 diabetes [43] and it may reflect the increase in the serum levels of fetuin-A and alterations in the changes in the permeability of glomerular capillaries. Fetuin-A is reported to pass through the slit diaphragm and re-introduced to proximal tubular cells by megalin-mediated endocytosis [44]. Zhou et al also reported that urinary exosomal fetuin-A was increased in the rats treated with cisplatin injection and in the ICU patients with acute kidney injury [45].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated PTH levels can also stimulate cytosolic free calcium concentrations, whereas metabolic acidosis results in decreased lumenal citrate, an important inhibitor of calcium phosphate precipitation (73, 99). Inflammation and deficiencies of inhibitors of calcification (i.e., fetuin-A) in combination with these imbalances in phosphorus homeostasis create a perfect storm for ectopic calcification, which can manifest in the vasculature and in the renal parenchyma (113, 116, 117, 138, 149). …”
Section: Dysregulation Of Phosphorus Homeostasismentioning
confidence: 99%
“…Nephrocalcinosis in 6-week-old male Wistar rats was induced by continuous injection of rat PTH 1-34 (Bachem, Bubendorf, Switzerland) at a dosage of 40 mg/kg per day via an osmotic mini-pump (Alzet, Cupertino, CA) for 50 hours. 50 L-LyszHCl or glycine at a dose of 20 mmol/kg was administered via a gastric tube at 2 hours, 14 hours, 26 hours, and 38 hours after the implantation of the osmotic pump.…”
Section: Animalsmentioning
confidence: 99%
“…5,50,51 All rats were handled in a humane manner in accordance with the guidelines of the Animal Committee of Osaka University. Figure 6.…”
Section: Animalsmentioning
confidence: 99%